Managing Integrative Holistic Early Childhood Education in Resource-Limited Contexts: A Case Study of a ‘Satu Atap’ Kindergarten in Indonesia - Martha Lasniroha Simanjuntak; Syaiful Eddy; Muhammad Fahmi (Yayasan Sembilan Pemuda Indonesia, 2026)
This case study examines the implementation of integrative holistic early childhood education (IH-ECE) management at a ‘Satu Atap’ kindergarten in suburban Indonesia, where limited resources and farming community characteristics create unique implementation challenges. Drawing on in-depth interviews with the principal and teachers, participatory observation, and document analysis, we analyze how the institution operationalizes the four management functions (planning, organizing, actuating, controlling) within the constraints of high teacher-student ratios (1:20), dual educator roles, and limited technology. Findings reveal that despite resource limitations, the institution demonstrates best practices including child-centered planning, center-based environmental organization, and continuous supervision through reflective practice. However, implementation gaps exist between principal and teacher perspectives, and external stakeholder involvement in evaluation remains limited. Through SWOT analysis, we identify six priority strategies: human resource capacity strengthening, resource optimization, technology utilization, partnership strengthening, monitoring and evaluation system development, and learning organization cultivation. The study contributes to understanding how IH-ECE principles translate into practice in resource-constrained settings and offers implications for policy and practice in similar contexts across the Global South.